Analyzing the demographic factors affecting overweight and obese dogs - Hudson, Emily (My University, 2025)
Obesity is the most common form of malnutrition among U.S. dogs. The Association for Pet Obesity Prevention reported that 59% of U.S. dogs are overweight or obese (APOP, 2022). With an estimated 84 to 89 million dogs inhabiting 45% of U.S. households, increasing dog ownership underscores the need for effective obesity mitigation strategies (AVMA Pet Ownership and Demographics Sourcebook, 2022). Obesity, characterized by an increase in adipose tissue beyond the ideal body fat range of 15% to 20% (Hand, Thatcher, Remillard et al., 2010). Obesity predisposes dogs to numerous adverse health consequences, shortening lifespan, inflating veterinary costs for owners, and compromising the quality of life of the dogs (Kealy et al., 2002; Lund et al., 2006). In Chapter 2 the 1000 Dog Study, findings revealed that overweight and obese dogs comprised 48% of senior participants, with no significant age or sex differences noted in weight categorization. This suggests that sex and intact factors may not be definitive determinants of weight status among senior dogs. Overweight and obese dogs exhibited significantly higher averages of comorbid conditions, including oral, dermatological, neoplastic, musculoskeletal, cardiovascular, urinary/renal, ocular, and neurological disorders. Conversely, healthy, ideal-weight senior dogs consumed 100% of their daily food as commercial dry or wet food, attributed to the ease of accurate portioning and the ability to tailor feeding based on the dog's weight status. Notably, overweight and obese dogs had higher triglyceride levels, indicating excessive caloric consumption and adipose tissue accumulation. Blood parameter assessments showed greater white blood cell and neutrophil counts in overweight and obese dogs, suggestive of an inflammation-related or immune response tied to increased adiposity. Chapter 3 of the Geo Study found that 60.7% of U.S. and Canadian dogs had been previously diagnosed as overweight and/or obese by veterinarians. Spayed females and neutered males were significantly more likely to be overweight or obese, whereas intact females were less likely to be diagnosed as overweight or obese, implying hormonal influences on weight stability. An analysis of dietary intake found that dry food consumption was significantly associated with a reduced obesity prevalence, while home-cooked food correlated positively with obesity. Supplement usage analyses found that the absence of supplements correlated with reduced obesity risk, although it was not significant post-adjustment. Overweight and obese dogs were more predisposed to mobility issues, skin conditions, digestive problems, stress disorders, and oral health conditions. Moreover, household demographics played a role in the weight status of dogs. Owners over 25 years of age, those with employment, and those earning over $45,000 annually were more likely to have overweight or obese dogs, reflecting the socio-economic complexities surrounding dog obesity. Geo Study survey results found a disparity between perceived and actual weight classifications among dog owners, with many owners misjudging the weight status of their dogs. Owner misclassification points to gaps in awareness or denial regarding the body condition of their dogs. The two studies highlight the multifaceted nature of canine obesity, influenced by genetic, dietary, health, and owner-perception factors, underscoring the importance of early diagnosis and intervention. Effective veterinary guidance is crucial in educating dog owners about viewing obesity as a preventable condition and implementing necessary nutritional and lifestyle modifications to mitigate associated health risks.
Keywords: Canine obesity; Overweight dogs; Canine weight management; Demographics of obese dogs; Obesity risk factors dogs